A comparison of the Functional Movement ScreenTM and the Landing Error Scoring System: A cohort study. Issue 1 (19th January 2020) - Tran, Andrew A.; Shen, Jennifer; Wernecke, Chloe; Gatewood, Corey T.; Harris, Alex H.S.; Dragoo, Jason L.
Abstract : Background: The Functional Movement Screen (FMS TM ) is a nonspecific movement pattern assessment while the Landing Error Scoring System (LESS) is a screen for movement patterns associated with lower extremity injury. The purpose of this study was to determine if the LESS and FMS TM are correlated or if they can be used as complementary assessments of preseason injury risk for anterior cruciate ligament injury. Methods: FMS TM and LESS were used to conduct a cohort study of 126 male National Collegiate Athletic Association Division IA football players. One hundred and eleven players met the criteria for inclusion during data review. At risk and not at risk LESS scores of players and FMS TM exercise score status were compared using Welch's t-test. Associations between FMS TM composites and LESS scores were evaluated using linear regression. Results: The average LESS score was 5.51±1.34, and the average composite FMS TM score was 11.77±2.13 (max=15). A poor FMS TM squat score (≤1 or asymmetry present) was associated with a higher LESS score ( P <0.001). No other FMS TM individual exercise score was associated with an at-risk LESS score ( P >0.05). Composite FMS TM score was loosely associated with the LESS score (R-squared=0.0677, P =0.006). Prior history of an ACL injury and player position were not associated with LESS score on multivariate regression ( P >0.05). Conclusions: The LESS and FMS TM are not well correlated and may serve as complementary assessments for preseason injury risk. Level of Evidence: Level III.